Effect of Interlayer Thickness on Mechanical Properties of Steel/Polymer/Steel Laminates Fabricated by Roll Bonding Technique (Global Journals of Research in Engineering, 2024)
Nowadays metal polymer metal laminates are extensively used in various industries due to their unparalleled properties In this study the roll bonding process was employed for lamination of low carbon steel St14 and semi-melted thermoplastic polyurethane sheets The T-peel and Single Lap Shear SLS tests were conducted to determine the optimal rolling speed to achieve the highest bond strength between the polymer core and the steel skins Then with the goal of investigation of the effect of polymer volume fraction on the mechanical properties of laminates the lamination process was performed at the optimal rolling speed and various thickness reductions The uniaxial tensile tests were conducted at three directions of 0 45 and 90 with respect to rolling direction for the skin sheet and four different laminates The results of both T-peel and SLS tests recommend the lowest rolling speed 25 rpm to acquire maximum bond strength The results of tensile tests show that the mechanical properties of the laminates depend on the sample direction It is also observed that as the volume fraction of the polymer in the laminate structure increases the yield strength tensile strength and elastic modulus decrease The bond strength of the metal polymer interface is directly related to the ductility behavior of the laminates
Keywords: metal/polymer/metal laminate sheet; roll bonding; thermoplastic polyurethane; low carbon steel sheet; mechanical properties